Variación de electrolitos pre y postactividad física en deportistas que practicas baloncesto y natación en la Federación Deportiva de Loja. - Jerves Torres, María Ibet (2013)
A suitable concentration of electrolytes such as sodium, potassium, calcium and magnesium in the internal medium, represent a key point for an adequate response osmotic balance in the body. During exercise, the production of large quantities of sweat, together with the variety of nutritional intake may in combination, promote antagonistic responses compared to the plasma concentration of these ions. Therefore, the present study aims to determine the levels of electrolytes Sodium, Potassium, Magnesium and Calcium in basketball and swimmers before and after physical activity, in the Loja Provincial Sports Federation, likewise determine electrolyte values players at 2 months in physical activity on the first shot; compare electrolyte values of the first month in relation to the values obtained in the second month, and disseminate these results to the people who participated in this research. We applied a method Cross-sectional and laboratory techniques to obtain relevant information for each component and whether or not there were changes in electrolytes. We analyzed 34 samples of athletes undergoing physical workload, obtained results it was determined that: in the first month in pre physical activity sodium values increased by 15%, potassium decreased by 3% , calcium decreased by 12%, and the magnesium were normal values; in post exercise sodium values decreased by 32%, the values of 12% potassium, calcium in a 17.65% and magnesium by 15%, in the second month was determined electrolyte values which were significantly reduced in sodium :: by 9% in the potassium 3% and 9% calcium, magnesium remained normal values, Likewise we compared two months of electrolytes in the players and there are significant variations decrease. Key words: physical load, electrolytes